2022
DOI: 10.3389/fendo.2021.802463
|View full text |Cite
|
Sign up to set email alerts
|

LINC00467 Is Upregulated by DNA Copy Number Amplification and Hypomethylation and Shows ceRNA Potential in Lung Adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is the most common histological lung cancer, and it is the leading cause of cancer-related deaths worldwide. Long noncoding RNAs (lncRNAs) have been implicated in tumorigenesis. LINC00467 is a novel lncRNA that is abnormally expressed in several cancer types including LUAD. However, its function and regulatory mechanism in LUAD progression remain unclear. In this study, based on The Cancer Genome Atlas data mining, we demonstrated that DNA copy number amplification and hypomethylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…"Tandem of pore domain in a weak inwardly rectifying K + channels (TWIK)" pathway involves two genes of the magenta module, including KCNK7 and KCNK1 . Wen Wang and colleagues 114 constructed a ceRNA network, and they concluded that KCNK1 is specific to LINC00467 in Lung adenocarcinoma. The "Tight junction interactions" pathway involves three genes of the magenta module containing PRKCI, CLDN20 , and PARD6G .…”
Section: Discussionmentioning
confidence: 99%
“…"Tandem of pore domain in a weak inwardly rectifying K + channels (TWIK)" pathway involves two genes of the magenta module, including KCNK7 and KCNK1 . Wen Wang and colleagues 114 constructed a ceRNA network, and they concluded that KCNK1 is specific to LINC00467 in Lung adenocarcinoma. The "Tight junction interactions" pathway involves three genes of the magenta module containing PRKCI, CLDN20 , and PARD6G .…”
Section: Discussionmentioning
confidence: 99%
“…Through bioinformatic analysis, two potential prognostic biomarkers (BARX2 and BCL9) for LUAD were revealed. ( Wang et al, 2021 ) Based on the results of these reports, LINC00467 stands as a potential diagnostic and prognostic biomarker, as well as a suitable therapeutic target for LUAD.…”
Section: Molecular Mechanism Of Linc00467 In Diverse Human Cancersmentioning
confidence: 99%
“…RT-qPCR assays were used to measure LINC00467 expression in 35 paired LUAD and adjacent normal lung tissues and researchers revealed that the expression level of LINC00467 in LUAD tissues was increased compared with that in adjacent normal lung tissues [22]. Wang et al [23] analyzed Fig. 1 LINC00467 expression in various cancers online sequencing data from the TCGA LUAD cohort and observed a positive correlation between LINC00467 DNA copy number values and LINC00467 mRNA expression.…”
Section: Linc00467 In Carcinomas Lung Cancermentioning
confidence: 99%
“…1 LINC00467 expression in various cancers online sequencing data from the TCGA LUAD cohort and observed a positive correlation between LINC00467 DNA copy number values and LINC00467 mRNA expression. Subsequently, they assessed the independent prognostic value of LINC00467 copy number alterations in terms of tumor metastasis and overall survival which predict poor prognosis in LUAD [23].The high expression of LINC00467 promoted the proliferation, migration, stemness, invasion of lung cancer cells and modulated cell cycle arrest and apoptosis [16,[19][20][21][22]24]. These results suggested that LINC00467 played an oncogenic function and performed an important role in LUAD development.…”
Section: Linc00467 In Carcinomas Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation